2010
DOI: 10.1016/s1684-1182(10)60081-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Genes Encoding Resistance to Macrolides, Lincosamides and Streptogramins Among Clinical Staphylococcal Isolates in a Turkish University Hospital

Abstract: This study investigated the prevalence of genes encoding resistance to macrolides, lincosamides and streptogramins (MLS(B)) among staphylococci in a series of 301 erythromycin-resistant clinical isolates of Staphylococcus aureus and coagulase-negative staphylococci (CoNS). Erythromycin-resistance phenotypes were determined according to Clinical and Laboratory Standards Institute guidelines and specific resistance genes erm(A), erm(B), erm(C), msr(A) and msr(B) were identified using polymerase chain reaction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
16
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 17 publications
10
16
0
2
Order By: Relevance
“…The ermA gene was the resistance determinant detected most frequently in S. epidermidis isolates, and similar results have been reported by other authors (Ardic et al, 2005). However, this result is in contrast to other findings, where the ermC gene was the main resistance determinant observed in CNS, including S. epidermidis (Lim et al, 2002;Cetin et al, 2010). In this study, only one isolate had the ermB gene, which has been detected by other groups in a low percentage of staphylococci (Hamilton-Miller & Shah, 2000;Chaieb et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…The ermA gene was the resistance determinant detected most frequently in S. epidermidis isolates, and similar results have been reported by other authors (Ardic et al, 2005). However, this result is in contrast to other findings, where the ermC gene was the main resistance determinant observed in CNS, including S. epidermidis (Lim et al, 2002;Cetin et al, 2010). In this study, only one isolate had the ermB gene, which has been detected by other groups in a low percentage of staphylococci (Hamilton-Miller & Shah, 2000;Chaieb et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, two isolates in our study harbored the linA gene. These results are also supported by recent findings, which showed that the linA gene was rarely detected in S. aureus strains [17,38,39].…”
supporting
confidence: 90%
“…Our finding did not show any msrA gene that is similar to the two available studies from Iran (17,33). However, different low rates of msrA gene have been reported by other researchers (16,38,40).…”
Section: Discussionsupporting
confidence: 84%
“…Based on the findings of our study and some other studies, no ermB gene has been found in studied isolates of S. aureus (17,33,38). But in 3 studies conducted in France, Brazil, and Turkey, the frequency of ermB gene was 0.7%, 2.2%, and 8.3%, respectively (16,39,40).…”
Section: Discussionsupporting
confidence: 57%